A Hybrid Software Architecture Evaluation Method for Dynamic System Development Method - Awan, R.; Muhammad, S. S.; Fahiem, M. A.; Awan, S. (The Nucleus, 2016)
Quality is an important paradigm while delivering software. Past traditional models have many problems. Agile process models overcome these problems, but these models are facing many challenges. The main challenge is the absence of proper Software Architecture Evaluation Method (SAEM) for agile models. It is essential to improve quality of agile models because these methods are lacking quality requirement, well defined software architecture and verified design. Without proper evaluation, these models suffer from severe quality and maintenance issues. Architecture evaluation is known as a standard to evaluate the quality of product. This study focuses on the development of a hybrid SAEM for agile process model. Dynamic System Development Method (DSDM) is a framework of agile methodology. This framework delivers a quality product in a short time. It is very important to improve quality of DSDM phases. Pre-project, project life-cycle and post-project are the phases of DSDM. It is required to apply a hybrid SAEM in phases of DSDM. By applying a hybrid SAEM on DSDM, the quality of DSDM phases may be improved. This improvement may be in term of quality attributes which are well defined in early life cycle. Furthermore, the quality attribute requirements are best satisfied due to well-formed software architecture design. A survey has been conducted in the software industry to validate this model.